Molecular Dynamics Study on Crystallization Patterns in Tunnel Drainage Pipes in Alkaline Geological Environments. (30th September 2022) - Chen, Xiangge; Zhou, Jie; Zhang, Xuefu; Yu, Wenbing; Liu, Shiyang; Liu, Hongyi; Xiao, Yuhan
Abstract : In the alkaline geological environment, crystallization blockage of tunnel drainage systems is a common engineering problem and it is difficult to treat. The microscopic mechanism of crystallization and the environmental influence factors are still unclear. Based on the molecular dynamics (MD) technique, this study establishes nanoscale models of CaCO3 and the polyvinyl chloride (PVC) pipe, which is commonly used in drainage systems, under different alkaline environments. The goal is to study the interfacial interaction between CaCO3 and PVC and to reveal the effect of the alkaline environment on the adsorption of CaCO3 by PVC at the atomic scale. Analysis of the adsorption properties predicted by the CaCO3 -PVC MD model reveals that CaCO3 molecules attract each other and form many atomic clusters at approximately 0.11 nm from the PVC interface. The peak difference between the strongly alkaline solution and the pure water solution at this distance reaches 31.6%. An in-depth exploration of the differences in adsorption between CaCO3 and PVC under different alkaline environments indicates that the mobility of CaCO3 rises gradually as the alkalinity of the solution increases. In particular, the mobility of CaCO3 in strongly alkaline solutions is approximately 60% higher than that in pure water. Moreover, as the alkalinity of the solution increases, the binding energy of the interface increases, the affinity of the interface increases, and the CaCO3 adsorption capacity gradually increases. The results of laboratory experiments were consistent with the MD simulation results, which indicates that MD simulation can play an important role in the design and evaluation of engineering practice. The innovation of this paper is to try to use the molecular dynamic (MD) technique in the field of materials to explain the practical problems in the field of traditional civil engineering, and the feasibility of molecular dynamic simulation is verified by indoor simulation experiments. The findings of this study can help for a better understanding of crystallization patterns in tunnel drainage pipes in alkaline geological environments and attempt to provide a theoretical basis and new ideas for solving this problem.